Outcome of pallidal stimulation of idiopathic generalized dystonia with predominant mobile truncal dystonia: case report. (4th May 2022) - Shalash, Ali; Fayed, Zeiad Y.; Hamid, Eman; Radwan, Hesham; Nada, Mohamed A.; Eid, Mohammed; Abdel Ghany, Walid A.
Abstract: Background: Further reports are required to describe the outcome of truncal dystonia treated by bilateral pallidal stimulation (globus pallidus interna deep brain stimulation [GPi-DBS]), owing to the small number of reports and clinical variability and complexity of truncal dystonia. Retrospectively, we report our experience of treating three patients with idiopathic generalized dystonia, with predominant mobile truncal dystonia by bilateral GPi-DBS. Methods: Three patients with idiopathic generalized dystonia underwent bilateral GPi-DBS. One patient had adult-onset dystonia, while two patients had childhood-onset dystonia. All patients had predominant mobile truncal dystonia of mixed abnormal postures (camptocormia and lateral tilt), while one patient had also truncal twist. Patients were assessed pre- and post-GPi-DBS using the Burke–Fahn–Marsden Dystonia Rating Scale (BFMDRS) and Dystonia Disability Scale (DDS). Results: The three patients showed marked improvement of global (94.78%, 92.4% and 80.95%) and truncal BFMDRS (all abnormal postures) (87.5%, 93.75% and 87.5%) and DDS (95.84% and 50%), using high amplitude monopolar settings, with a dramatic improvement of the mobile component. Improvement was persistent for 1.5, 3 and 6 years. Conclusion: Bilateral GPi-DBS improves markedly the mobile truncal dystonia and associated abnormal postures in patients with adult and childhood-onset idiopathic generalized dystonia. Improvement was persistent for up to 6 years.